Vander's Human physiology : the mechanisms of body function. - Widmaier, Eric P.; Raff, Hershel, 1953-; Strang, Kevin T.; Vander, Arthur J., 1933- (Boston : McGraw-Hill Higher Education, 2008)
"Vander's Human Physiology, Twelfth Edition, carries on the tradition of clarity and accuracy, while refining and updating the content to meet the needs of today's instructors and students. The twelfth edition features a streamlined, clinically oriented focus to the study of human body systems. It has also responded to reviewer requests for more clinical applications. Chapter 19 was new for the eleventh edition, with three complete case studies. The twelfth edition will contain an additional new case study. Additional Physiology Inquiries have been added to many figures throughout the chapters. These critical-thinking questions are just one more opportunity to add to the student's learning experience.
Ch.1. Homeostasis: A framework for human physiology -- Ch.2. Chemical composition of the body -- Ch.3. Cellular structure, proteins, and metabolism -- Ch.4. Movement of Molecules across cell membranes -- Ch.5. Control of cells by chemical messengers -- Ch.6. Neuronal signaling and the structure of the nervous system -- Ch.7. Sensory physiology -- Ch.8. Consciousness, the brain, and behavior -- Ch.9. Muscle -- Ch.10. Control of the body movement -- Ch.11. The Endocrine system -- Ch.12. Cardiovascular physiology -- Ch.13. Respiratory physiology -- Ch.14. The kidneys and regulation of water and inorganic Ions -- Ch.15. The Digestion and absorption of Foods -- Ch.16. Regulation of Organic Metabolism and energy balance -- Ch.17. Reproduction -- Ch.18. Defense mechanism of the Body -- Ch.19. Medical Physiology: Integration using clinical cases.
Keywords: Physiology; Human physiology -- Textbooks